Istiṭālah Fī ʿIrḍ al-Muslim dalam Perspektif Hadis: Analisis Takhrij, Kebahasaan, dan Relevansinya di Media Sosial: Istiṭālah Fī ʿIrḍ al-Muslim in the Hadith Perspective: An Analysis of Takhrij, Linguistics, and Its Relevance to Social Media - Wilda Ana Chamidah; Ahmad Fudhaili (AL ISNAD: Journal of Indonesian Hadith Studies, 2026)
This study aims to examine the prohibition of degrading others’ honor in the perspective of hadith, focusing on the narration “inna min arbā al-ribā al-istīṭālata fī ʿirḍ al-muslim bi ghayri ḥaqqin.” This research employs a qualitative method with a library research approach, including hadith authentication (takhrij), linguistic analysis of key terms, and examination of classical hadith commentaries. The findings reveal that violating a person’s honor (ʿirḍ) is considered a major sin with a high degree of prohibition, as it involves تجاوز (exceeding limits) in exposing or exaggerating others’ faults. However, Islam does not entirely prohibit criticism; rather, it regulates it through strict ethical boundaries. In certain circumstances, mentioning others’ shortcomings is permissible when it serves a legitimate Sharīʿah-based purpose, such as reporting injustice, seeking legal advice, preventing wrongdoing, offering sincere counsel, and providing necessary warnings or identification. The practice of the Prophet SAW demonstrates that criticism can be delivered objectively, proportionally, and for the sake of public benefit without degrading individual dignity. Therefore, this study emphasizes that Islamic communication ethics require a balance between preserving honor and conveying truth, particularly in the context of freedom of expression in the modern era.